New reactions of diazene and related species for modelling combustion of amine fuels. (17th September 2021) - Marshall, Paul; Rawling, George; Glarborg, Peter
Abstract : Potential energy surfaces for reactions involving N 2 H 2 isomers of diazene (diimide) have been explored using density functional theory, with energies based on coupled-cluster theory. A focus is on processes that create or consume these species, and isomerisation between the E (trans) and Z (cis) forms of HNNH. These include isomerisation and dissociation pathways for HNNH, addition of H atoms to form N 2 H 3, abstraction by H atoms yielding short-lived NNH, and abstraction reactions of H with N 2 H 3 . Transition state and capture theories are applied for high-pressure-limiting behaviour, while low-pressure and falloff regions are characterised via the methods of Troe and coworkers. Rate constants and thermochemistry are provided to improve models of diamine chemistry, relevant to the combustion of NH 3 especially at high concentrations, high pressures or under reducing conditions. Results indicate that amine radical recombination mainly yields the E HNNH isomer, while H-abstraction from N 2 H 3 results in E HNNH and H 2 NN. However, at elevated temperature E → Z isomerisation becomes competitive, and Z HNNH, being more reactive, acts to enhance the diazene consumption rate. GRAPHICAL ABSTRACT: UF0001